2019
DOI: 10.1016/j.crhy.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Physics Of Opinion Formation: Is it a SPOOF?

Abstract: We present a short review based on the nonlinear q-voter model about problems and methods raised within statistical physics of opinion formation (SPOOF). We describe relations between models of opinion formation, developed by physicists, and theoretical models of social response, known in social psychology. We draw attention to issues that are interesting for social psychologists and physicists. We show examples of studies directly inspired by social psychology like: "independence vs. anticonformity" or "perso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 123 publications
(313 reference statements)
2
82
0
Order By: Relevance
“…. (40) We see that within the Landau approach we have obtained exactly the same value as previously in Equation (14). The transition is continuous as long as B > 0 and for B < 0 it is discontinuous, so we obtain the tricritical point from the condition:…”
supporting
confidence: 72%
See 2 more Smart Citations
“…. (40) We see that within the Landau approach we have obtained exactly the same value as previously in Equation (14). The transition is continuous as long as B > 0 and for B < 0 it is discontinuous, so we obtain the tricritical point from the condition:…”
supporting
confidence: 72%
“…Results obtained here has encouraged us to design a laboratory experiment, based on the idea introduced in [41], to check how the size of the influence group impacts the level of anticonformity. However, it is too soon to provide more details of this project, as reported in [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because all binary models, mentioned above, have been extensively investigated for years, many modifications and extensions of their original formulations have been proposed; a short review on modifications of the majorityvote model can be found in [29], on the Watts threshold model in [30], on the q-voter model in [31] and on the Galam model comprehensive review has been written by the author of the model [32,33]. Among many extensions, going into different directions, the introduction of an additional type of the social response was particularly interesting from the point of view of social/psychological sciences, as well as the theory of non-equilibrium phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Most well-known models of opinion dynamics seem to imply that a stable fixed state, either consensus or polarization, is inevitable [1][2][3][4][5][6][7]. However, local and spatial heterogeneity and ongoing exchange of opinions and cultural traits is a characterizing feature of social systems.…”
Section: Introductionmentioning
confidence: 99%